Saharan desert dust radiative effects: a study based on atmospheric modelling. (3rd February 2011) - Santos, D.; Costa, M.J.; Silva, A.M.; Salgado, R.; Domingues, A.; Bortoli, D.
This work investigates the Saharan desert storms direct effect, through the assessment of regional-scale Desert Dust (DD) aerosol Radiative Forcing (RF). Simulated parameters, obtained from atmospheric modelling, are used. The effect over different surfaces on the dust RF is analysed and the stratospheric ozone is considered. In the presence of DD aerosols, a shortwave cooling and a longwave warming effects are found both at the top of the atmosphere and at the surface. The underlying surface seems to interfere in the aerosol RF and the total ozone column changes have small impact on the dust RF at the surface.